(untitled) (Journal of Science and Technology, 2016)
The Lethal Yellowing Disease locally referred to as the “Cape St Paul Wilt Disease” is the single most important disease that has devastated several hectares of coconut plantations in Ghana. Two decades of coconut screening for tolerant planting material has identified the Sri Lankan Green Dwarf crossed Vanuatu Tall (SGD x VTT) coconut hybrid as the most promising planting material in the context of disease. To provide farmers with planting material that has high dis- ease tolerance and also good agronomic characteristics, the study compared some basic traits of the coconut hybrid with other important coconut varieties with the objective of determining the suitability of the SGD x VTT as alternative planting material to revamp the coconut industry in Ghana. Mean sample size of 25 palms per coconut variety under the study was analyzed us- ing two sample t-test procedure. The study indicated that the yield performance of the SGD x VTT coconut hybrid was better than the tall coconut types including the local West African Tall (WAT) and compared favourably with the Malayan Yellow Dwarf crossed Vanuatu Tall (MYD x VTT) coconut hybrid. The good agronomic characteristics of the SGD x VTT coupled with its high resistance to the CSPWD proved its suitability as alternative planting material to revamp the coconut industry in Ghana.